Ram pressure in jellyfish galaxies interacting with sloshing cold fronts - Santos, Elvis Amandio de Mello Terencio dos (2025)
Cluster mergers are the most energetic phenomena in the present-day Universe. These interactions often substantially disturb the intracluster medium (ICM), creating regions with density and temperature discontinuities, such as sloshing spirals. There is evidence that such environments can influence galaxy evolution. This study aims to understand how a galaxy that crosses an environment with discontinuities in density and temperature can be affected. To this end, a set of simulations was conducted using a wind tunnel setup into which a galaxy was inserted. A total of eight models were created, namely two control runs and six with distinct density and temperature transitions along the tunnel, composing simulations with low density and high density environments. Results show that galaxies lose more gas due to the higher density encountered when crossing denser and discontinuous regions in comparison to a constant density environment. The star formation rate exhibits a brief enhancement when the galaxy enters the denser section of the tunnel and color index also undergoes slight changes, initially becoming bluer. However, even in the simulations with the most intense transitions, changes are not substantial (below 5%) in relation to the control models. By the end of the simulation, SFR and color index are similar to the control runs. These results suggest that crossing ICM discontinuities can induce measurable effects in a galaxy, but these are subtle and short-lived.